H− formation in collisions of hydrogen atoms with Al(100) surfaces - Obreshkov, Boyan; Thumm, Uwe (My University, 2013)
We theoretically investigate the electron transfer dynamics during the reflection of hydrogen atoms on an Al(100) surface for a wide range of collision energies below 6 keV. We find a nonmonotonic variation of the hydrogen-negative-ion fractions as functions of the projectile impact velocity due to nonadiabatic electron transfer. Our calculated anion fractions for projectiles scattered along high Miller-index crystal-surface directions are in good quantitative agreement with measured H− fractions for a wide range of exit velocities.